Polar vortex weakening and its impact on surface temperature in recent decades - Kim, Seong-Joong; Choi, Hyesun (Polar Research, 2024)
The stratospheric polar vortex (SPV) weakening is linked to surface circulation changes. This study employs statistical analysis using reanalysis data to compare the anomalous SPV behaviour in the Northern (NH) and Southern (SH) hemispheres and its downward impacts on surface climate. The onset of annual SPV weakening occurs in mid-January and late September in the NH and SH hemispheres, respectively. Following the onset of SPV weakening, stratospheric polar cap height (PCH) anomalies were strongly correlated with tropospheric PCH anomalies. Significant cold anomalies were observed over Eurasia within 30 days after SPV weakening onset in the NH, whereas warming responses occurred in the SH 30–60 days after onset over Antarctica, except in the Antarctic Peninsula. These contrasting surface temperature responses to SPV weakening events in both hemispheres are the results of changes in the geopotential height in the troposphere, reminiscent of the change in geopotential height in the lower stratosphere, with a trough over Eurasia in the NH, and a higher height anomaly over East Antarctica in the SH. SPV changes have played a role in modulating surface climate via a downward influence on tropospheric circulation in recent decades. Even though they show a weakening trend in both hemispheres, SPV changes cannot fully explain long-term temperature trends. This is partially because SPV trends observed during the analysis period are relatively weak. This study enhances our understanding of the characteristics of the SPV coupled with troposphere circulation and can contribute to improved surface weather forecasting.